4-Dimensional intravital microscopy: a new model for studies of leukocyte recruitment and migration in hepatocellular cancer in mice - Takeichi, Takayuki; Engelmann, Guido; Mocevičius, Paulius; Schmidt, Jan; Ryschich, Eduard (Journal of gastrointestinal surgery, 2010)
Although it is accepted that the immune system plays a role in the prognosis of hepatocellular carcinoma (HCC), the exact mechanisms of leukocyte recruitment into HCC are poorly understood. Progress in the study of this aspect has been hindered by technical limitations.
Gesehen am 14.09.2023